USE GAME FORMS IN THE STUDY OF DISCIPLINE «СONTROL AND REVISION IN BUDGETARY AND FINANCIAL ESTABLISHMENTS» - Карпенко, Н. Г. (Scientific Progress & Innovations, 2014)
Introduction of interactive teaching methods in professional disciplines enables to change the attitude to learning object, turning it into a subject. The student becomes a co-author lectures, seminars, etc. In the article the procedure for applying interactive forms of education for the education in the students such qualities of the future specialist that facilitate the implementation of their tasks, the development of complex analytical, forecasting, innovation and organizational communication skills.